Recurrent stroke in a child with TRMA syndrome and SLC19A2 gene mutation - Karimzadeh, Parvaneh; Moosavian, Toktam; Moosavian, Hamidreza; kiumarsi, Azadeh (Iranian Journal of Child Neurology, 2018)
Here we report a 5-month-old boy with thiamine Responsive Megaloblastic Anemia syndrome (TRMA syndrome) with several attacks of stroke. In addition to the cardinal clinical manifestations of the syndrome (thiamine-responsive megaloblastic anemia, diabetes mellitus, and sensor neural hearing loss), the patient showed the ischemic attack of stroke. Megaloblastic anemia and Diabetes were diagnosed at 8 months and was successfully treated with vitamin and insulin prescription. After treatment of thiamine diabetes was controlled and insulin was discontinued. In spite of the thiamine administration, the second stroke as hemorrhagic stroke was occurred in the patient after a few months. TRAMA is inherited in an autosomal recessive manner. TRMA was confirmed by mutation in SLC19A2. A homozygous splice site variant was detected in SLC19A2 gene. According to our knowledge stroke was not reported in this syndrome (only in one report about one attack in an adult patient) but in this patient several attacks of stroke was report before and after thiamin administration.